Computer‐assisted valve in valve in a deteriorated Mosaic valve using a library of bioprostheses. Issue 6 (19th November 2020) - Belhaj Soulami, Reda; Castro, Miguel; Haigron, Pascal; Verhoye, Jean‐Philippe
Abstract: Valve‐in‐valve (ViV) procedures have emerged from an off‐label procedure to a safe and efficient alternative to redo aortic valve replacement in the treatment of symptomatic structural valve deterioration (SVD). During ViV procedures, optimal placement of the transcatheter heart valve (THV) inside the degenerated bioprosthesis is of paramount importance regarding complications such as device embolization, coronary obstruction, periprosthetic regurgitation, residual gradients, and mitral valve injury, but also for the attainment of optimal hemodynamics. In the case of the Mosaic (Medtronic, Minneapolis, MN) valve, the limited radiopaque landmarks represent a challenge to a reproducible, optimal implantation. Such implantation may require multiple contrast injections and transesophageal echocardiogram (TEE) guidance. We herein describe a computer‐assisted ViV procedure inside a deteriorated Mosaic valve, achieving reproducible optimal placement using a preacquired library of bioprostheses 3D models. Our approach suggests an evolving paradigm in ViV procedures, from safe and efficient toward optimal therapy for symptomatic SVD.